CORPUS-ASSISTED DISCOURSE STUDY (CADS): WOMEN WITH DISABILITIES IN KOMPAS.COM’S NEWS REPORTING - Yenny Karlina (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
The interaction of gender and disability has gained attention in academia and activism, emphasizing the importance of combating prejudice and stigma encountered by women with disabilities. The portrayal of this group in the media is critical because it has the potential to either perpetuate stereotypes or contribute to constructive societal change. The study, "Corpus-assisted discourse study (CADS): Women with disabilities in Kompas.com's News Reporting," addressed how one of Indonesia's prominent news websites, Kompas.com, portrayed and discussed women with disabilities in its news reporting. This study conducted a descriptive qualitative study concerning the corpus-aided discourse study (CADS) approach. It used the web scraping of Octoparse to build a sizable news corpus from Kompas.com. Then, AntcConc, a corpus toolkit, generated 26,398 tokens from news items with the keyword phrase perempuan disabilitas (women with disabilities). The findings indicated 45 occurrences of perempuan (women) and disabilitas (disability) associated with the lexical words: ganda (multiple), seksual (sexual), kekerasan (violence), diperkosa (raped), etc. Meanwhile, concordance analysis of the corpus revealed different topic clusters in the news reports: violent crimes and challenges relating to policies for women with disabilities. This study also shed insights on the unintentional potential ramifications for readers' cognitive biases in the discourse that Kompas.com propagated through news reporting.